Minorities and Persecution - Välimäki Reima (Routledge, 2025)
The history of minorities in the Middle Ages is characterised by alternating periods of persecution and uneasy coexistence. The main dividing line between the majority and minority was not ethnicity but religion. Jews and Muslims were religious minorities whose existence in Christian realms was permitted on condition that strict segregation was maintained between religious groups. The reason was practical: forced conversion or mass expulsions of conquered Muslim populations were not plausible solutions. The attitudes towards Jews turned increasingly hostile in the Late Middle Ages, resulting in mass expulsions from, for example, England, France, and Spain. Christian heresies were not tolerated, but ecclesiastical and secular authorities persecuted heretical groups with few exceptions. Many heretics were not from minority groups but were individual religious radicals; the Cathars and Waldensians especially developed a social structure and sense of identity and shared history, in part formed by the Church’s persecution, and can be considered religious minorities. Other types of minorities were ethnic groups living at the margins of Christendom and interacting with it, such as the Sámi in northern Fennoscandia and, from the fifteenth century onwards, various ‘Gypsy’ groups arriving from the Ottoman Empire into Eastern and Western Europe. Although sexual minorities were not defined groups of people or identities in the Middle Ages, those deviating from sexual norms were occasionally persecuted. Scholarship has approached violence against minorities both as a defining development and characteristic of medieval European culture and as a political conflict and negotiation at the level of individual communities. In either case, minority history is not only about marginal groups but also about how the majority defined itself against ‘the other’. The historiography of Iberia has debated whether convivencia or conflict was characteristic of medieval Spain. The greatest challenge in the study of minorities is that most of the sources were written from a hostile perspective. Therefore, scholars have developed a range of strategies to interpret sources such as inquisition depositions and polemical treatises.
Routledge Resources Online – Medieval Studies